Research on the Direction of Innovation and Entrepreneurship Education Reform Within the Digital Media Art Design Major in the Digital Economy - Yu, Wenhui; Jiang, Tan (Frontiers in Psychology, 2021)
This research aims to analyze and explore the methods and paths of deep integration of innovation and entrepreneurship education and professional education of the major of digital media art design. This research adopts the grounded theory research method, and takes the leaders of digital media art design major in colleges and universities and five successful entrepreneurs whose major was digital media art design and have certain achievements in the industry after graduation as the research objects. This paper comprehensively finds out the main problems of digital media art design major in cultivating innovative and entrepreneurial talents. Through the analysis and clustering of the scope and structure of the original data collection, this paper establishes a theoretical model of the innovation and entrepreneurship education reform path of the major of digital media art design, the internal key of elements the theoretical model including professional talent training mechanism, curriculum integration mechanism, teacher team construction mechanism, and resource support mechanism, and the school enterprise cooperation mechanism is recognized to be the external key elements of innovation and entrepreneurship education reform path model. The research results provide a directional reference for the education and teaching reform and professional construction of the major of digital media art design, so as to help the major of digital media art design to cultivate more high-level pioneering professionals to adapt to the transformation and upgrading of economic and social development.